Postmodernity Grounded - Stipe Grgas ([sic], 2011)
The following contribution to a discussion that purports to “rethink the humanities” stems from the field of American Studies which has, since its beginnings, challenged and put pressure on disciplinary borders and institutional structures of both the humanities and the social sciences. The approaches it has espoused has led observers to see it as a domain of inquiry where virtually anything goes. One of the explanations that has been put forth to account for the heterogeneity of both the research agendas and the multiplicity of methods within American Studies is the dynamics of demography within the United States and the way that this dynamic has impacted both the enrollment statistics at American universities and the diversifications of its teaching staff. According to this oft-repeated view, the research agenda of American Studies reflects the stages of empowerment of the different groups making up the United States polity. Although one would be hard put not to acknowledge these, distinctly American, developments, on the present occasion my point of departure is a more general rationale which American Studies, like other disciplines today, rely upon when setting their research agenda and deploying their methods: in simplest terms, they harbor a desire and feel a need for relevancy.